Revealing the status of Orbicella: Main reef-builder of Morrocoy National Park and Cuare Wildlife Refuge, Venezuela, Southern Caribbean. - Anaurora Yranzo-Duque; Ana Teresa Herrera-Reveles; Estrella Villamizar; Francoise Cabada-Blanco; Jeannette Pérez-Benítez; Hazael Boadas; José G Rodríguez Quintal; Carlos Pereira; Samuel Narciso; Freddy A Bustillos (PLoS ONE)
Reef-building corals are the main basis of coral reef ecosystems, and the Orbicella genus is currently the most important in the Caribbean region. Although Orbicella species have been extensively studied, gaps in some southern Caribbean areas still exists on their status, which is crucial for management and conservation plans. In this study, we aimed to describe the population status of Orbicella faveolata and Orbicella annularis in two coastal Marine Protected Areas (MPA) of Venezuela: Morrocoy National Park and Cuare Wildlife Refuge. Between 2018-2020, 16 reefs in five sectors were surveyed using the Atlantic and Gulf Rapid Reef Assessment Protocol. Among the two Orbicella species, O. faveolata was dominant in both MPA´s with higher densities and live cover, varying at both reefs and sectors. The central sector of Morrocoy and reefs from Cuare are the most relevant for Orbicella populations, due to the higher live cover and abundance of reproductive colonies. Diseases were the primary threat recorded for both species. Adequate MPA management is essential for the conservation of the Morrocoy-Cuare coral system, including the reduction of local anthropogenic stress sources, such as oil spills, uncontrolled tourism and sewage discharges.